Unlocking the gut-liver axis: microbial contributions to the pathogenesis of metabolic-associated fatty liver disease - Buchynskyi, Mykhailo; Kamyshna, Iryna; Halabitska, Iryna; Petakh, Pavlo; Kunduzova, Oksana; Oksenych, Valentyn; Kamyshnyi, Oleksandr (Frontiers in Microbiology, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is a complex metabolic disorder characterized by hepatic lipid accumulation and subsequent inflammation. This condition is closely linked to metabolic syndrome and obesity, with its prevalence rising due to sedentary lifestyles and high-calorie diets. The pathogenesis of MAFLD involves multiple factors, including insulin resistance, lipotoxicity, oxidative stress, and inflammatory responses. The gut microbiota plays a crucial role in MAFLD development, with dysbiosis contributing to liver inflammation through various mechanisms, such as enhanced intestinal permeability and the translocation of bacterial products like lipopolysaccharide (LPS). Microbial metabolites, including short-chain fatty acids (SCFAs) and bile acids, influence hepatic function and immune responses, with potential implications for disease progression. Specific gut microbiome signatures have been identified in MAFLD patients, offering potential diagnostic and therapeutic targets. Moreover, gut-derived toxins, such as endotoxins, lipopolysaccharides, trimethylamine-N-oxide and bacterial metabolites, significantly influence liver damage and inflammation, highlighting the complex interplay between the gut microbiome and hepatic health. This review comprehensively examines the complex interplay between the gut microbiota and MAFLD, focusing on underlying pathogenic mechanisms, potential biomarkers, and emerging microbiome-targeted therapeutic strategies for disease management.